Pengaruh Gaya Kepemimpinan, Kerjasama Tim dan Budaya Organisasi terhadap Prestasi Kerja pada PT. Kencana Sawit Indonesia - Ramadhi Ramadhi; Edo Andrefson; Yozi Putri Sakinah; Juli Adevia; Oza Syafriani (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2023)
This research aims to determine leadership style, teamwork and organizational culture simultaneously on work performance of PT employees. Indonesian Palm Oil Calendar. This research uses quantitative methods with a sample of 97 employees using a saturated sampling technique. The research results showed that there was a positive and significant influence of leadership style on work performance, there was a positive and significant influence of teamwork on work performance, there was a positive and significant influence of organizational culture on work performance and there was a positive and significant influence of leadership style, teamwork and organizational culture together on work performance. The contribution of leadership style, teamwork and organizational culture to work performance is 0.683 or 68.3% while the remaining 40.6% is determined by other variables not analyzed in the model in this study.